Corporal punishment and its effects in children - Rimal, Hem Sagar; Pokharel, Archana (Journal of Kathmandu Medical College, 2014)
Corporal punishment in children is still a major problem throughout the globe and more common in developing countries like Nepal. Several researches done across the globe have clearly established the fact that use of corporal punishment at home, school or alternative settings is associated with higher prevalence of externalizing behaviour of youth, substance use, depression, juvenile delinquency, poor academic performance and marital conflict as an adult. Authors have reviewed the journals, websites and books to find out the magnitude of problem in the national as well as international context. It has also looked at the long-term and short term adverse effects of corporal punishment in children, current legislative status, and suggested strategies to discipline children. Reinforcing legal actions against this practice can contribute to expedite the process to end corporal punishment of children globally with strong advocacy from paediatricians and other health professionals.Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9968Uploaded date : 3/4/2014